2015
DOI: 10.1080/1331677x.2015.1022390
|View full text |Cite
|
Sign up to set email alerts
|

Exploring consumers’ food-related decision-making style groups and their shopping behaviour

Abstract: The purpose of this research is to develop consumer typology, classify consumers by using food-related decision-making styles and link the resulting typology with consumer shopping behaviour. A modified Sproles and Kendall's CSI instrument was used to identify decision-making styles in food-product context in Croatia. The data obtained from the survey was analysed using factor, cluster and ANOVA analyses. Three groups of consumers were identified: Recreational, Novelty-driven and Economic consumers. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…When item loadings are compared with previous studies, a number of differences reveal. For example, two items loaded negatively on the recreational-hedonistic factor in Sproles & Kendall (1986) and Anic et al (2015) studies, were found to load on a different additional factor in this study. This factor was labeled as "time spent for shopping", similar to the study of Ünal & Erciş (2006) who labeled the factor as "giving time for shopping and enjoy it".…”
Section: Demographic Characteristics Of the Respondentsmentioning
confidence: 83%
See 1 more Smart Citation
“…When item loadings are compared with previous studies, a number of differences reveal. For example, two items loaded negatively on the recreational-hedonistic factor in Sproles & Kendall (1986) and Anic et al (2015) studies, were found to load on a different additional factor in this study. This factor was labeled as "time spent for shopping", similar to the study of Ünal & Erciş (2006) who labeled the factor as "giving time for shopping and enjoy it".…”
Section: Demographic Characteristics Of the Respondentsmentioning
confidence: 83%
“…The current study adjusted these items in consumer styles inventory with consumers' decision on food products. Since Anic et al (2015) had studied on consumers' food related decision making styles before, the current study also used their measurement scale in order to harmonize the items in consumer style inventory with food products choices. Eight-factor model including 40-items, adopted into food products is presented in Appendix A.…”
Section: Questionnaire Design and Measuresmentioning
confidence: 99%
“…Research on Consumer Decision-Making (CDM) styles are important for companies since they determine consumer behaviour (Anić, Rajh, & Piri-Rajh, 2015). It is relevant in examining cross-cultural consumer behaviour (Mitchell & Bates, 1998) in market segmentation (Walsh, Hennig-Thurau, Wayne-Mitchell, & Wiedmann, 2001).…”
Section: Specialisation In Tourism As a Results Of Social And Economicmentioning
confidence: 99%
“…Previous studies have shown different food-related decision-making styles (Ani c et al, 2015), as well as the different reasons that motivate consumers in purchasing local food. According to Weatherell et al (2003) motives can be broadly divided into Ad 1.)…”
Section: Literature Reviewmentioning
confidence: 99%